Thalassaemia Registries: A Call for Action. A Position Statement from the Thalassaemia International Federation. (4th July 2022) - Farmakis, Dimitrios; Angastiniotis, Michael; El Ghoul, Maria-Melina; Cannon, Lily; Eleftheriou, Androulla
Abstract: Disease registries can be extremely powerful evidence generating tools while providing a central meeting point for all implicated stakeholders, facilitating their networking and interaction. Registries can play a major role in addressing the challenges that the care of thalassemia patients is currently facing. By collecting updated and representative data on disease burden, features, management and outcomes at local, national, regional and global level, thalassemia registries can allow the evaluation and bench marking of provided healthcare services, the detection of unmet clinical needs and the identification of inequalities in healthcare delivery. A total of 17 thalassemia registries has been in place since 1984, being characterized by heterogeneity and incomplete geographic coverage. Representativeness, interoperability, harmonization, quality assurance and sustainability are important features that thalassemia registries should pursue. The Thalassaemia International Federation (TIF) aims at promoting the coordination and collaboration in existing thalassemia registries and the establishment of new ones, with a particular focus on areas of emerging economies. In this regard, TIF has undertaken the design, development and implementation of a web-based platform to host a global thalassemia registry.